2019
DOI: 10.30802/aalas-cm-18-000001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azithromycin on Behavior, Pathologic Signs, and Changes in Cytokines, Chemokines, and Neutrophil Migration in C57BL/6 Mice Exposed to Dextran Sulfate Sodium

Abstract: Here we characterized the murine dextran sulfate sodium (DSS) model of acute colitis. Specifically, we evaluated azithromycin and metronidazole treatment regimens to assess their effects on animal wellbeing, pathologic changes, barrier function, cytokine and chemokine profiles, and neutrophil migration in colon tissue. Azithromycin treatment significantly reduced the severity of colitis, as assessed through body weight change, water consumption, macroscopic lesions, and animal behaviors (activity level, climbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…With respect to the effect of azithromycin on neutrophils, Bystrzycka et al revealed that azithromycin decreased NET release in activated neutrophils in vitro ( Bystrzycka et al, 2017 ). Anderson et al demonstrated that azithromycin inhibited neutrophil migration in dextran sulfate sodium-induced mice ( Anderson et al, 2019 ). However, Cavalcanti et al showed that hydroxychloroquine and azithromycin did not alter disease progression in patients with mild-to-moderate COVID-19 ( Cavalcanti et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…With respect to the effect of azithromycin on neutrophils, Bystrzycka et al revealed that azithromycin decreased NET release in activated neutrophils in vitro ( Bystrzycka et al, 2017 ). Anderson et al demonstrated that azithromycin inhibited neutrophil migration in dextran sulfate sodium-induced mice ( Anderson et al, 2019 ). However, Cavalcanti et al showed that hydroxychloroquine and azithromycin did not alter disease progression in patients with mild-to-moderate COVID-19 ( Cavalcanti et al, 2020 ).…”
Section: Drugs Targeting Neutrophils For Covid-19 Associated Ardsmentioning
confidence: 99%
“…The quantity of Collagen I, III and IV are all significantly reduced in human aneurysms compared to non-aneurysmal acute ruptured porcine samples. Reassuringly there is good reproducibility of quantification between porcine and human non-aneurysmal samples as shown in earlier studies [ 4 13 ].…”
Section: Discussionmentioning
confidence: 54%
“…Using a physiological model, results could identify patterns in radiological, pathological, and histological changes that affect the aorta under stress. Although no studies apart from Surman et al [ 1 ] have reported on the maximal pressures obtained in the porcine aortic root and ascending aorta, many studies have showed that a porcine model is effective in the application of cardiopulmonary bypass and replicating models applicable to human subjects in cardiothoracic surgery [ 4 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for local anti-inflammatory effects of macrolides in populations suffering from IBD is hard to find. Preclinical evidence exists suggesting potential use of macrolides as immunomodulators in gut inflammation (Anderson et al, 2019). Intriguingly, it has been shown with the murine dextran sulfate sodium colitis model that single early-life treatment with antibiotics, including the macrolide tylosin, can disturb the gut microbial environment sufficiently to exacerbate subsequent IBD later in life (Ozkul et al, 2020).…”
Section: G Other Diseasesmentioning
confidence: 99%